2010
DOI: 10.1557/proc-1265-aa06-04
|View full text |Cite
|
Sign up to set email alerts
|

Geo-descriptive Modeling of Water Conducting Features Characterized in Sedimentary Formations in Horonobe Area of Japan

Abstract: A three-dimensional (3-D) discrete fracture network (DFN) geo-descriptive model is developed for water conducting features (WCFs) in the sedimentary formations of Horonobe underground research laboratory (URL) in Japan. Fracturing and faulting system in/around the URL area, which is the main investigation area of the Horonobe URL project, is characterized by taking into account borehole geophysical logging data, regional geologic/structural data, and fracture/fault data (orientation, intensity, size) obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Because bedding planes have different orientations from borehole to borehole, they were rotated into the horizontal plane to enable an analysis of the fault orientations. This analysis showed that the most common orientation of faults in the boreholes was nearly vertical, with a WNW–ESE to NW–SE strike [ Hatanaka et al , 2010; Lim et al , 2010]. Typically, where fracture orientations are widely distributed in folded sedimentary rocks, but concentrated in a specific orientation in unfolded strata, such fractures are likely to have been formed by regional tectonic stress prior to folding [e.g., Lorenz et al , 1991; Silliphant et al , 2002; Mynatt et al , 2009].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Because bedding planes have different orientations from borehole to borehole, they were rotated into the horizontal plane to enable an analysis of the fault orientations. This analysis showed that the most common orientation of faults in the boreholes was nearly vertical, with a WNW–ESE to NW–SE strike [ Hatanaka et al , 2010; Lim et al , 2010]. Typically, where fracture orientations are widely distributed in folded sedimentary rocks, but concentrated in a specific orientation in unfolded strata, such fractures are likely to have been formed by regional tectonic stress prior to folding [e.g., Lorenz et al , 1991; Silliphant et al , 2002; Mynatt et al , 2009].…”
Section: Analysis and Discussionmentioning
confidence: 99%